Influences of Personal Traits in the Process of Information Searching - Karunanayake, K.G.D.A. (My University, 2008)
Many influencing factors in the information search process have been identified in this research area. Among them, cognitive and psychological variables as the personal traits which make intellectual influences are commonly addressed. Here knowledge, skill and psychological elements are focused upon as key factors of this personal trait. The study empirically examined the influences of personal traits in the process of information searches. The survey was conducted with the undergraduates of the faculty of Medicine at the University of Colombo (Sri Lanka) in January 2007. Based on the influence of the three elements of personal traits (knowledge, skills and psychological factors) the students’ positions in the search process were identified. The mean/median value used for the data analysis indicated the influence levels of each trait. The survey results indicated that a few students exhibited traits strongly tied to the level of their success, while the majority of them did not expertly search due to negatively or moderately influenced personal traits. Positive influences rarely occurred. A consideration of the influence levels made it clear that some paucity areas of KSP limited the success of those students.